The Cardiac Physiome: perspectives for the future. - Bassingthwaighte, J; Hunter, P; Noble, D (2009)
The Physiome Project, exemplified by the Cardiac Physiome, is now 10 years old. In this article, we review past progress and future challenges in developing a quantitative framework for understanding human physiology that incorporates both genetic inheritance and environmental influence. Despite the enormity of the challenge, which is certainly greater than that facing the pioneers of the human genome project 20 years ago, there is reason for optimism that real and accelerating progress is being made.